Dynamic VM allocation and traffic control to manage QoS and energy consumption in cloud computing environment. (22nd July 2019) - Hanini, Mohamed; Kafhali, Said El; Salah, Khaled
In the last few years, cloud computing technology has revolutionised the IT industry. However, the guarantee of the desired Quality of Service (QoS) and the power consumption control are two of the major challenges that this paradigm poses. In this paper, we propose a mechanism combining a scheme for virtual machine utilisation with a mechanism to control the access for incoming requests to the virtual machine monitor. The number of activated virtual machines is defined according to the workload, and the control access is based on the number of requests. The studied mechanism and its performance parameters are described by a mathematical model, and a power consumption model is built and evaluated. Numerical examples evaluating QoS parameters are given. Moreover, the impact of the proposed mechanism on the behaviour of energy consumption is evaluated. Analysis of the obtained results shows the positive impact of the proposed mechanism.